2015
DOI: 10.1007/s00787-015-0688-2
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary findings on associations between moral emotions and social behavior in young children with normal hearing and with cochlear implants

Abstract: Moral emotions such as shame, guilt and pride are the result of an evaluation of the own behavior as (morally) right or wrong. The capacity to experience moral emotions is thought to be an important driving force behind socially appropriate behavior. The relationship between moral emotions and social behavior in young children has not been studied extensively in normally hearing (NH) children, let alone in those with a hearing impairment. This study compared young children with hearing impairments who have a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 50 publications
1
36
0
6
Order By: Relevance
“…According to the researchers, better social skills are related to more frequent expressions of positive emotions (Wiefferink et al 2012). Ketelaar and Wiefferink (2015) observed a poorer understanding of moral emotions, such as shame and guilt, and poorer ability to relate them to social functioning in children with HI when compared with NH children. Wiefferink et al (2012) stated that if emotion-regulation strategies do not develop well in the early years of life, optimal strategies cannot be learned later in life.…”
Section: Vocal Emotion Identification By Children Using Cochlear Implmentioning
confidence: 83%
See 1 more Smart Citation
“…According to the researchers, better social skills are related to more frequent expressions of positive emotions (Wiefferink et al 2012). Ketelaar and Wiefferink (2015) observed a poorer understanding of moral emotions, such as shame and guilt, and poorer ability to relate them to social functioning in children with HI when compared with NH children. Wiefferink et al (2012) stated that if emotion-regulation strategies do not develop well in the early years of life, optimal strategies cannot be learned later in life.…”
Section: Vocal Emotion Identification By Children Using Cochlear Implmentioning
confidence: 83%
“…A lack of caretaker support may also affect the development of the child's sense of security: An inability to tolerate stress may lead to a sense of insecurity and the withdrawal from social situations (Fox & Calkins, 2000). Caretakers can support the development of their children's emotions by validating and labelling the emotions, teach coping strategies, and helping them to improve their regulatory skills (Eisenberg et al, 2010;Ketelaar & Wiefferink, 2015). Selfawareness develops by the age of two, and starting from the age of three, children with normal hearing (NH) begin to internalize moral standards and to channel their emotional behavior without their caretakers' guidance (Ketelaar & Wiefferink, 2015).…”
Section: Vocal Emotion Identification By Children Using Cochlear Implmentioning
confidence: 99%
“…It is plausible that improvements in cognitive skills, such as perspective taking, could aid the development of understanding the meaning of subtle emotion expressions (Choudhury, Blakemore, & Charman, 2006). For example, in a recent study, Ketelaar, Wiefferink, Frijns, Broekhof, and Rieffe (2015) found that 4-5-year-old deaf children with CIs displayed moral emotions (shame, guilt and surprise) to a lesser degree than hearing children. Therefore, future studies could explore the role that intensity plays in the recognition of these more complex emotions.…”
Section: Discussionmentioning
confidence: 99%
“…Emotion vocabulary. The Emotion Vocabulary Questionnaire is a parent report that measures children's knowledge of emotional words (Ketelaar et al, 2015). Parents rated whether their child knew and used 20 emotion and mental state words (0 = no/1 = yes).…”
Section: Emotion Control and Emotion Recognition The Emotionmentioning
confidence: 99%